Ethical considerations of using generative Artificial Intelligence in advertising - Ratnasari, Eny; Sumartias, Suwandi (PRofesi Humas, 2025)
Background: The Ministry of Communication and Digital Affairs created an advertising campaign for the “Makan Bergizi Gratis” Program. This advertisement drew much criticism from netizens because it used generative AI. Netizens considered the use of AI disrespectful to local animators and Indonesia’s creative industry. Purpose: This study aimed to determine the network and classification of comments on the AI-generated advertisement of “Makan Bergizi Gratis” released on YouTube by the Ministry of Communication and Digital Affairs. Methods: This study adopted a quantitative-qualitative (mixed method) approach with two methodological tools: social network analysis and content analysis. Results: Comments on the advertisement of “Makan Bergizi Gratis” are dominated by argumentative, critical comments directed at the Ministry of Communication and Digital Affairs. In this criticism, netizens expressed disappointment due to the use of generative AI in the advertisement, which devalued animators and human-made animation works. Conclusion: Based on the analysis of the comments, netizens are divided into three groups: individuals who understand that the advertisement is AI-generated and call it generative AI; individuals who understand that the advertisement is AI-generated and call it AI animation; and individuals who call it animation. The researchers also concluded that Indonesians are struggling to distinguish between animation, generative AI, and AI. Implications: Policymakers, communication practitioners, and academics must share the vision that the development and use of generative AI require a strong framework of communication ethics to guide responsible practices. This research could also be an evaluation source for the Ministry of Communication and Digital Affairs. It could trigger all creative industry players in Indonesia to formulate a code of ethics for using generative AI in Indonesia.